1962
DOI: 10.1007/bf02633350
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a standardized detergency evaluation method

Abstract: This paper describes a standardized laboratory procedure for determining the fabric soil‐removal efficiency of heavy‐duty detergents. A careful analysis of machines, standard soil fabrics, operating times, and water hardness had led to the standardization of technique. The precision of the method has been presented for tests carried out in hard and soft water on two anionic heavy‐duty detergents at a concentration of 0.2%. Standard deviations of 0.74% for a water hardness of 50 p.p.m. and 1.03% for a water har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1962
1962
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…21,40,41 Germain 42 noticed that some factors such as temperature, agitation speed and the amount of detergent should be taken into consideration in optimizing laundering conditions. Linfield et al 43 proved that an increase in washing time, agitation speed or a detergent concentration contributed to better fabric detergency performance. They observed the maximum detergency at approximately 150-170 rpm and 15-20 min washing cycle for washing conditions at the temperature of 48.9 C, a concentration of a detergent of 0.2% and 135 ppm water hardness.…”
mentioning
confidence: 99%
“…21,40,41 Germain 42 noticed that some factors such as temperature, agitation speed and the amount of detergent should be taken into consideration in optimizing laundering conditions. Linfield et al 43 proved that an increase in washing time, agitation speed or a detergent concentration contributed to better fabric detergency performance. They observed the maximum detergency at approximately 150-170 rpm and 15-20 min washing cycle for washing conditions at the temperature of 48.9 C, a concentration of a detergent of 0.2% and 135 ppm water hardness.…”
mentioning
confidence: 99%
“…Linfield et al (11) conducted a detergency study using a Terg-O-Tometer and found that an increase in agitation speed, washing time, or detergent concentration produced better fabric detergency performance; for washing conditions at 48.9°C, 0.2% detergent, and 135 ppm water hardness, maximal detergency was observed at approximately 150-170 rpm and 15-20 min washing cycle. A Terg-O-Tometer is generally used in a bench-scale unit to simulate home washing-machine action.…”
mentioning
confidence: 99%
“…Tergotometer offers a simple and rapid evaluation of washing performance by producing a certain level of soil removal which is sufficient to reflect reasonably small formulation differences for one wash [31][32][33][34][35]. Therefore, Copley Scientific tergotometer was used for preparing both synthetic dye and small-scaled wastewater solutions for the study.…”
Section: Methodsmentioning
confidence: 99%